2013
DOI: 10.1109/tpami.2012.126
|View full text |Cite
|
Sign up to set email alerts
|

3D Face Discriminant Analysis Using Gauss-Markov Posterior Marginals

Abstract: We present a Markov Random Field model for the analysis of lattices (e.g., images or 3D meshes) in terms of the discriminative information of their vertices. The proposed method provides a measure field that estimates the probability of each vertex being "discriminative" or "nondiscriminative" for a given classification task. To illustrate the applicability and generality of our framework, we use the estimated probabilities as feature scoring to define compact signatures for three different classification task… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(11 citation statements)
references
References 23 publications
1
9
0
Order By: Relevance
“…Their results indicated that it is possible to recognize race information with only 3D mesh of human face. Similar results have been reported by Ocegueda et al [144], who also investigated finding the most discriminative regions of the face for 3D racial face classification. Using Gauss-Markov posterior marginals (GMPM) for computing discriminative map of subjects from BU-3DFE database (Asian/White), they performed cross validation on FRGC v2.0 for the aim of comparing with Toderci's work.…”
Section: D Facessupporting
confidence: 89%
“…Their results indicated that it is possible to recognize race information with only 3D mesh of human face. Similar results have been reported by Ocegueda et al [144], who also investigated finding the most discriminative regions of the face for 3D racial face classification. Using Gauss-Markov posterior marginals (GMPM) for computing discriminative map of subjects from BU-3DFE database (Asian/White), they performed cross validation on FRGC v2.0 for the aim of comparing with Toderci's work.…”
Section: D Facessupporting
confidence: 89%
“…These 40 wavelet packets were selected using Simulated Annealing [21]. Alternatively, Omar et al [22] developed a method to weight different parts of the face based on their discriminability. To forego such an expensive search, we propose a variation of LC-KSVD that learns a set of dictionary atoms which perform well in recognition for the training set.…”
Section: )mentioning
confidence: 99%
“…This assumption is specified by considering a Markovian priori distribution. Gauss Markov Measure Field (GMMF) [4] is one of the models that combines Bayesian estimation with Markov Random Field and it is used in many classification tasks, [5,6,7,8,10,11,12,13]. One of the main difficulties for GMMF, as for all methods based on the combination of Bayesian estimation and MRF for image segmentation, is the likelihood computation.…”
Section: Introductionmentioning
confidence: 99%